Exploring Transformative Leadership Approaches in Modern Educational Institutions - Sarong, Jelyn S (RIRAI Publisher, 2023)
This study examines transformative leadership within Philippine educational settings to discern its impact on student outcomes, staff development, and institutional effectiveness. A descriptive qualitative analysis involving diverse stakeholders revealed that transformative leadership diverges significantly from traditional management, emphasizing innovation, empathy, and adaptability. It fosters a culture where staff confidence and autonomy lead to professional growth and improved educational outcomes. In addition, the findings suggest that such leadership is essential for educational institutions navigating the complexities of modern education, including technological advancements and societal changes. Effective communication and systematic evaluation were identified as key for transformative leaders to measure and enhance student success, despite facing resistance to change. The study concludes that transformative leadership will become increasingly central in education, driving institutions towards inclusivity and a forward-thinking ethos. It was recommended that Philippine educational institutions adopt transformative leadership to bridge disparities, enhance quality, and prepare for future educational demands. The approach is particularly beneficial for public schools, higher education, TVET institutions, private educational providers, policymakers, and community learning centers, promising to elevate the quality of education in a rapidly evolving global landscape.